Review Article on “Ksharakarma and Agnikarma in Shalakya Tantra” - Arunima , N S (International Research Journal of Ayurveda & Yoga, 2024)
Ksharakarma and Agnikarma are two among the para surgical techniques mentioned in Ayurveda and are explained to provide complete relief in certain diseases which are not cured by herbal medicine or surgical interventions. According to Ayurveda Kshara is ‘Pradhanatama’ among Shastra and Anushastra, and Agni is ‘Shreshta’ among Anushastras. Our Ancient Acharyas described external and internal uses of Ksharakarma in various disorders in two forms- Pratisaaraneeya and Paaneeya; whereas based on the specific site, heat retention and transmission capacity different materials had prescribed to perform Agnikarma. The use of these two para-surgical procedures has been mentioned in the different contexts of Shalyatantra. This review article deals with various aspects of Kshara and Agnikarma in Netra- Karna- Nasa- Mukha and Shiroroga.